ADAT BERSENDI SYARAK, SYARAK BERSENDI KITABULLAH SEBAGAI LANDASAN PENGEMBANGAN PENDIDIKAN BAHASA ARAB BERBASIS KEARIFAN LOKAL MELAYU - A. MUALIF; IKRIMA MAILANI; SOPIATUN NAHWIYAH; ZULHAINI ZULHAINI; SHEILA RAHMA YANTI (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2026)
This study aims to analyze the philosophy of Adat Bersendi Syarak, Syarak Bersendi Kitabullah (ABS-SBK) as a foundation for developing Arabic language education based on Malay local wisdom and to examine its relevance in fostering contextual and character-oriented learning. This research employs a qualitative library research method. The data were collected from the Qur'an, Hadith, literature on Arabic language education, Malay culture, as well as relevant scholarly articles and legal documents. The data were analyzed using content analysis to explore the relationship between the values of ABS-SBK and the principles of Arabic language learning. The findings indicate that the ABS-SBK philosophy is highly compatible with the objectives of Arabic language education, particularly in integrating linguistic competence with religious, moral, and cultural values. The incorporation of Malay local wisdom into learning materials, teaching methods, instructional media, and assessment practices enhances the contextual relevance of learning, strengthens students’ cultural identity, and promotes moderate Islamic values and good character. Therefore, the development of Arabic language education based on the ABS-SBK philosophy not only emphasizes language proficiency but also serves as a means of preserving Malay cultural heritage and internalizing Islamic values that are relevant to the needs of contemporary society.